An analogy in the use of metformin, clomiphene citrate and letrozole: in the treatment of polycystic ovary syndrome (Research, Society and Development, 2022)
Polycystic ovary syndrome (PCOS) is one of the most common clinical conditions among endocrine disorders that affect women of reproductive age, accounting for about 80% of cases of anovulatory infertility. Objective to carry out a literature review on the use of metformin in the treatment of women with PCOS, making an analogy in the use of metformin, clomiphene citrate and letrozole. Methodology: The study is an integrated review of the literature as a reference for articles from the years 2013 to 2020 carried out in the databases: Medline, Lilacs, Scielo. Identified on 80 articles, used from 20 in the elaboration of the work. Results: Metformin was shown to be effective as a combination therapy with letrozole in the treatment of PCOS, but there was no consensus on its use as monotherapy.